Malaria in adults after the start of Covid-19 pandemic: an analysis of admission trends, demographics, and outcomes in a tertiary hospital in the Gambia - Sheikh Omar Bittaye; Abubacarr Jagne; Lamin E. S. Jaiteh; Alfred Amambua-Ngwa; Abdul Karim Sesay; Bertha Ekeh; Behzad Nadjm; Williams Estrada Ramirez; Asmell Ramos; Basil Okeahialam; Emmanuel Effa; Ousman Nyan; et al. (Malaria Journal, 2023)
Abstract Background Malaria remains a major public health concern in The Gambia. The study assessed the trend of malaria admissions and outcome of adult patients admitted after the start of the COVID-19 pandemic in a tertiary hospital in The Gambia. Methods This was a retrospective hospital-based study and data was collected from the 18th October 2020 to 28th February 2023. Demographic data, clinical features, investigations, treatment, and outcomes were recorded. Results A total of 499 malaria cases were admitted to the hospital over the 29 months of the study period. Data from 320 (67.2% of the total cases) adult patients admitted into the internal medicine department were analysed. The median age was 22 years, range (15–90) and 189 (59.1%) cases were youth with a youth (15–24 years) to older adult (> 24 years) ratio of 1.4:1. The majority of the patients were male 199 (62.2) with a male to female ratio of 1.6:1. The total number of malaria cases admitted into the internal medicine department increased from 103 cases in 2021 to 182 cases in 2022and admission peaked in November in both years. The total number of admitted malaria cases during the peak of the malaria season also increased from 92 patients between September 2021 and December 2021 to 132 patients from September 2022 to December 2022.There was also an increase in both severe and uncomplicated malaria during the same period. The total mortality was 31 (9.7%) and the rate was similar in 2021 9 (8.7%) and 2022 15 (8.4%). Patients with impaired consciousness were more likely to die when compared to those without impaired consciousness [19 (23.6%) vs 12 (5%), p  ≤ 0.001]. Patients with acute kidney injury were also more likely to die when compared with those without acute kidney injury [10 (20.4%) vs 15 (7.7%), p = 0.009]. Conclusion The findings show an emerging and consistent trend of malaria admissions and the outcome in the youth and older adult population after the start of the COVID-19 pandemic in The Gambia. This, therefore, suggests the need for the implementation of targeted malaria prevention interventions in this population to further prevent the spread of the disease to the more vulnerable population.